Nanocomposite catalytic membranes for energy production: Advances and challenges - Mubashir, M. (Elsevier, 2020)
In the past decade, hydrogen (H2) is considered as a renewable, alternative, and future clean fuel energy. Nevertheless, conventional methods such as methane oxidation, steam reforming, dry reforming, and water gas shift reaction used for the H2 production are complicated and expensive. Therefore innovation in nanoenabled membranes, particularly nanocomposite catalytic (NCC) membranes for H2 production are anticipated to accelerate the adoption of this energy-efficient technology in the industry. In this chapter, contemporary challenges in NCC membranes and the important aspects involved in the membrane development are reviewed. In addition, long-term durability and future prospects of NCC membranes in H2 production are highlighted. Furthermore, the advantages and limitations of mathematical models used for the prediction of H2 permeation are also discussed in this chapter. Overall, coupling of the catalyst, configuration of the catalyst, particle size, and conversion of reactants play an important role in the H2 production over the NCC membranes. Besides, it was found that the pulverized iron-chromium (Fe-Cr) based palladium (Pd) membrane showed the durability of 1200 h, which was the highest durability compared to the other catalyst-based NCC membranes reported in the literature. On the other hand, 1D, 2D, 2D-PH, and 3D models have been used to obtain the least percentage error for the process involving high H2 permeance values. Along with the existing models, new models could be developed in order to achieve lower absolute average error (AARE) between the experimental and simulated values for the combined reaction and separation of H2 production process. Â© 2021 Elsevier Inc. All rights reserved.